INDONESIA ENVIRONMENTAL DIPLOMACY IN PRESIDENT JOKO WIDODO’S ERA (2014-2019) OF THE ISSUE REJECTION INDONESIA’S CPO BY EUROPEAN UNION - Theresia Siahaan (Sociae Polites, 2020)
Environmental diplomacy is one of discipline in International Relations, which combines ecological problems involving other countries and uses negotiation as solutions. The policy of the European Commission through Renewable Energy Directive II for Indonesia put palm oil discriminated among another vegetable oil. This research found that in Joko Widodo’s era, Indonesia has carried out its role as an international agent with some policies related to managing sustainable palm oil. Indonesia also uses bilateral, multilateral, and global approaches, and even the involvement of international organizations as a peaceful way resolving palm oil disputes for the target of Sustainable Development Goals’ through palm oil. Keywords: Environmental Diplomacy, Palm Oil, Renewable Energy Directive II, European Union, Export, Rejection